An echo in the darkness - Rivers, Francine, 1947- (Rivers, Francine, 1947- Mark of the lion., 1994)
They knew her as Rapha, the healer. What they didn't know was that beneath the veils was a woman they had both loved . a woman who was supposed to be dead.